Oral Findings and Gustatory Function of Postmenopausal Indonesian Women with Low Levels of Reproductive Hormones - Lugito, Manuel (TALENTA, 2023)
Menopause is always associated with various problems in the mouth. This study aims to determine oral findings and taste function in postmenopausal women in Indonesia. Descriptive cross-sectional sample of 18 postmenopausal women aged between 53 and 89 years living in nursing homes. Data were collected through demographic questionnaires, oral examination, measuring total saliva volume, assessing saliva pH, checking estradiol and progesterone levels in the blood. Taste tests were carried out the next day with liquids of three different concentrations of four different taste qualities including sweet, salty, sour and bitter. Research results: average age of participants was 75.4+8.6 years, and average DMFT 16.06+2.59. Significant reductions were seen in pH and saliva flow rate, while the most common oral complaints were xerostomia (22%) and pain in the temporomandibular joint (11.1%). Mean estradiol levels were 1.5 + 4.4 pg/mL and progesterone 0.05 + 0.06 ng/mL. Burning Mouth Syndrome and Oral Candidiasis were not found. The majority reported a higher level of taste sensitivity, especially to solutions with the highest concentration, namely bitter taste. This research shows that subjects experienced changes in oral health due to hormonal changes, side effects of medication, and the aging process. Decreased taste function, especially sensitivity to salty, sweet and sour tastes. Â